About one model of modernization of the educational process (MMIT Proceedings, 2025)
The article discusses key directions in the modernization of the educational process through the integration of E-Learning and information and communication technologies (ICT). It explores technical and methodological aspects of implementing "smart classrooms", using digital educational resources, electronic textbooks, and multimedia tools. The authors emphasize the role of network-based learning, dual training systems, and personalized learning trajectories. The article analyzes how the incorporation of modern digital tools enhances the accessibility, flexibility, and quality of education